PENGARUH INISIASI MENYUSU DINI (IMD) DENGAN PRODUKSI ASI PADA IBU POST PARTUM DI RUANG BERSALIN PUSKESMAS MUBUNE KECAMATAN LIKUPANG BARAT - , Engryne Nindi, Michelle Kairupan (JURNAL ILMIAH KESEHATAN MANADO, 2023)
Air Susu Ibu (ASI) merupakan makanan alamiah yang ideal untuk bayi terutama pada bulan-bulan pertama kehidupan bayi. Tujuan dalam penelitian ini untuk Mengetahui Pengaruh Inisiasi Menyusu Dini Dengan Produksi ASI Ibu Post Partum di Ruang Bersalin Puskesmas Mubune Kecamatan Likupang Barat. Jenis penelitian menggunakan desain pre experimental dengan bentuk one group pre-post test design. Populasi dalam penelitian ini yaitu Ibu Post Partum di Puskesmas Mubune Kecamatan Likupang Barat periode bulan Januari –April dengan jumlah 16 respondene. Data di analisa menggunakan uji Wilcoxon Signed Rank Test dengan nilai kemaknaan α = 0,005. Berdasarkan hasil perhitungan Wilcoxon Signed Rank Test, maka nilai Z yang didapat sebesar – 3,464 dengan p value (Asymp. Sig 2 tailed) sebesar 0,001 dimana kurang dari nilai α = 0,05, Berarti H0 ditolak maka ada Pengaruh Inisiasi Menyusu Dini (IMD) Dengan Produksi ASI Pada Ibu Post Partum di Ruang Bersalin Puskesmas Mubune Kecamatan Likupang Barat. Kesimpulan dalam penelitian ini yaitu Produksi ASI Sebelum dilakukan Inisiasi Menyusu Dini pada Ibu Post Partum di Ruang Bersalin Puskesmas Mubune Kecamatan Likupang Barat Sebagian besar produksi ASI tidak lancar. Produksi ASI Setelah dilakukan Inisiasi Menyusu Dini pada Ibu Post Partum di Ruang Bersalin Puskesmas Mubune Kecamatan Likupang Barat Sebagian besar produksi ASI Lancar. Ada pengaruh inisiasi menyusu dini dengan produksi ASI ibu post partum di ruang bersalin Puskesmas Mubune Kecamatan Likupang Barat.   Kata kunci: Inisiasi Menyusu Dini (IMD), Produksi ASI, Ibu Post Partum         ABSTRACT   Breast milk (BM) is an ideal natural food for babies, especially in the first months of a baby's life. The benefits of breastfeeding are physiological and psychological benefits for mothers and babies. The gold standard of baby food starts from Early Initiation of Breastfeeding (EIB) within 30 to 60 minutes after the baby is born, exclusive breastfeeding to infants from birth to 6 months of age, starting to give complementary foods to breast milk since the baby is 6 months old, and continuing breastfeeding until children two years of age or older. The aim is to determine the effect of early initiation of breastfeeding on the production of breast milk for post-partum mothers in the Maternity Room of the Mubune Health Center, West Likupang District. The type of research used in this research is the design of this research is pre experimental in the form of one group pre-post test design. The population in this study were Post Partum Mothers at the Mubune Health Center, West Likupang District for the period from January to April with a total of 16 samples. The data were analyzed using the Wilcoxon Signed Rank Test with a significance value of = 0.005. Based on the calculation results of the Wilcoxon Signed Rank Test, the Z value obtained is -3,464 with a p value (Asymp. Sig 2 tailed) of 0.001 which is less than the value of = 0.05, Means that H0 is rejected then there is an Effect of Early Initiation of Breastfeeding (EIB)With Breast Milk Production in Post Partum Mothers in the Maternity Room of the Mubune Health Center, West Likupang District. The conclusion in this study is that the production of breast milk before the initiation of early breastfeeding for post partum mothers in the Maternity Room of the Mubune Health Center, Likupang Barat District, most of the milk production is not smooth. Breast Milk Production After Early Initiation of Breastfeeding for Post Partum Mothers in the Maternity Room of the Mubune Health Center, Likupang Barat District, most of the milk production was smooth. There is an Effect of Early Initiation of Breastfeeding on Breastfeeding Production of Post Partum Mothers in the Maternity Room of the Mubune Health Center, West Likupang District.  Keywords : Early Initiation of Breastfeeding (EIB), Breast Milk Production, Post Partum Mother Download Full File Disini